2003
DOI: 10.1021/ja0388820
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (±)-Didehydrostemofoline (Asparagamine A) and (±)-Isodidehydrostemofoline

Abstract: The first total syntheses of (+/-)-didehydrostemofoline (1) and (+/-)-isodidehydrostemofoline (3) are reported. The synthesis begins with the Diels-Alder reaction of readily available pyrrole 9 and ethyl (E)-3-nitroacrylate, the latter serving as a regioinverted equivalent of ketene. After hydrogenation to prevent retro-Diels-Alder reaction, the major cycloadduct is transformed to 7-azabicyclo[2.2.1]heptanol 14. Aza-Cope-Mannich reaction of the formaldiminium derivative of 14 delivers 1-azatricyclo[5.3.0.04.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 16 publications
2
69
0
3
Order By: Relevance
“…The saturated analogues of these compounds are reported to act as signaling substances in bacteria [6] and enhance spore formation in streptomycetes or induce metabolite production [7]. There has been a continuous interest in the development of efficient and convenient methodologies for the synthesis of butenolides [8] because they are attractive building blocks in natural product synthesis and comprise structural moieties present in large number of significant compounds such as alkaloids [9], lignans [10], insect pheromones [11], cardenolides [2], flavour components [12] and large number of synthetic drug candidates with diverse biological activities [13]. These valid observations encouraged the authors to undertake the synthesis of some new substituted α,β-unsaturated butenolides (4-11a,b) by a simple and convenient method involving the use of easily accessible and inexpensive chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The saturated analogues of these compounds are reported to act as signaling substances in bacteria [6] and enhance spore formation in streptomycetes or induce metabolite production [7]. There has been a continuous interest in the development of efficient and convenient methodologies for the synthesis of butenolides [8] because they are attractive building blocks in natural product synthesis and comprise structural moieties present in large number of significant compounds such as alkaloids [9], lignans [10], insect pheromones [11], cardenolides [2], flavour components [12] and large number of synthetic drug candidates with diverse biological activities [13]. These valid observations encouraged the authors to undertake the synthesis of some new substituted α,β-unsaturated butenolides (4-11a,b) by a simple and convenient method involving the use of easily accessible and inexpensive chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges arise when the inverse orientational selectivity of the DA reaction is desired, as demonstrated by Overman and coworkers in their synthesis of (AE)-didehydrostemofoline (asparagamine A) and (AE)-isodidehydrostemofoline (Scheme 12). [92] In their approach, an ideal route from pyrrole 82 to key intermediate 84 would employ a DA reaction with nitroethylene (45) (or equivalent); however, owing to the mismatched electronic properties of the two components, 83 is not accessible. Instead, a less direct route was taken, using dienophile 85.…”
Section: Acrylatesmentioning
confidence: 99%
“…6 Owing to their complex molecular architecture and intriguing biological activity, the stemofoline alkaloids have attracted considerable synthetic attention, 11-14 culminating in two racemic total syntheses. 15,16 The studies reported herein comprise the first non-racemic synthesis of the fully oxygenated tricyclic core of the stemofoline alkaloids.…”
Section: Introductionmentioning
confidence: 99%